Perbezaan Di Antara Mushaf-Mushaf Al-Quran: Sorotan Terhadap Aspek Ilmu Dhabt Al-Quran : Differences Between Qurʾān Copies (Mushaf): Highlights on Aspects of Dhabt Of Qurʾān - Abd Muhaimin bin Ahmad (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The Qurʾān is recited by Muslims using different variations. The differences in the recitation require a separate printing of the Qurʾān copies (mushafs) that match the recitation of each riwayah. Observation on these mushafs found that the differences occur not only in terms of reading variations but also in scripts (rasm), signs (dhabt), determination of verses (fawasil), determination of divisions (tahzib), as well as signs related to stop and continue recitation (waqf and ibtida'). Insensitivity to these differences can cause a misperception that there are errors and mistakes in the mushaf, which is the holy book of Muslims. Thus, the objectives of this paper are to identify the differences between the mushafs in terms of the sign (dhabt) and make a comparison in the matter between the mushafs. This study utilised the qualitative method using observation, analysis and comparison on the mushafs of the Qurʾān and books that are considered as main references in the science of dhabt of Qurʾān. Among the important findings of this study are differences in the aspect of dhabt, which include differences in nuqat al-i’jam involving three letters namely nun, fa and qaf. Differences also occur in nuqat al-i’rab, including the signs of dhammah, tanwin, sukun, the signs of idgham naqis, hamzah wasal and lam alif. This matter occurs due to differences in sources and practices between the schools of masyariqah and magharibah in the placement of signs in the Qurʾān. If the differences are unrecognised, they may lead to the presumption of errors in the printing of the Qurʾān.